Rapid room-temperature synthesis of a porphyrinic MOF for encapsulating metal nanoparticles - He, Huihui; Li, Luyan; Liu, Yang; Kassymova, Meruyert; Li, Dandan; Zhang, Liangliang; Jiang, Hai-Long (Nano research, 2021)
While metal nanoparticles (NPs) have shown great promising applications as heterogeneous catalysts, their agglomeration caused by thermodynamic instability is detrimental to the catalytic performance. To tackle this hurdle, we successfully prepared a functional and stable porphyrinic metal-organic framework (MOF), PCN-224-RT, as a host for encapsulating metal nanoparticles by direct stirring at room temperature. As a result, Pt@PCN-224-RT composites with well-dispersed Pt NPs can be constructed by introducing pre-synthesized Pt NPs into the precursor solution of PCN-224-RT. Of note, the rapid and simple stirring method in this work is more in line with the requirements of environmental friendly and industrialization compared with traditional solvothermal methods.